2015
DOI: 10.1073/pnas.1510245112
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-B-Neuropilin-1 signaling is spatiotemporally indispensable for vascular and neuronal development in zebrafish

Abstract: Physiological functions of vascular endothelial growth factor (VEGF)-B remain an enigma, and deletion of the Vegfb gene in mice lacks an overt phenotype. Here we show that knockdown of Vegfba, but not Vegfbb, in zebrafish embryos by specific morpholinos produced a lethal phenotype owing to vascular and neuronal defects in the brain. Vegfba morpholinos also markedly prevented development of hyaloid vasculatures in the retina, but had little effects on peripheral vascular development. Consistent with phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 44 publications
(62 reference statements)
2
23
0
Order By: Relevance
“…Intriguingly, the vascular disruption observed in znf408 mutants seemed to be specific to the hyaloid/retinal vasculature. This is in line with other studies demonstrating specific requirements for PI3K, 30 VEGF-B, 31 or vitamin D 32 in the development of the hyaloid vessels in zebrafish. The specific role of these signaling pathways and whether they constitute different points in the same pathway or contribute to several independent pathways that converge on regulating retinal vascular development is an area of future investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, the vascular disruption observed in znf408 mutants seemed to be specific to the hyaloid/retinal vasculature. This is in line with other studies demonstrating specific requirements for PI3K, 30 VEGF-B, 31 or vitamin D 32 in the development of the hyaloid vessels in zebrafish. The specific role of these signaling pathways and whether they constitute different points in the same pathway or contribute to several independent pathways that converge on regulating retinal vascular development is an area of future investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Mirroring previous reports of vegfaa expression, vegfaa:EGFP fish displayed EGFP fluorescence in developing somites, indicating that vegfaa regulatory sequences faithfully report domains of endogenous vegfaa (SI Appendix, Fig. S1 A and B) (20)(21)(22)(23)(24). During cardiac development, the expression domain for Vegfa varies among…”
Section: Resultssupporting
confidence: 62%
“…Angiogenesis inhibitors now constitute a clinical anticancer strategy . Vascular endothelial growth factor is considered a key mediator of angiogenesis and a promising therapeutic target in cancer . Our results showed that Notch4 silencing downregulated the expression of VEGF.…”
Section: Discussionmentioning
confidence: 58%